2001
DOI: 10.1007/3-540-45540-x_5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Communication on the Performance of Co-allocation

Abstract: In systems consisting of multiple clusters of processors interconnected by relatively slow connections such as our Distributed ASCI 1 Supercomputer (DAS), jobs may request coallocation, i.e., the simultaneous allocation of processors in different clusters. The performance of co-allocation may be severely impacted by the slow intercluster connections, and by the types of job requests. We distinguish different job request types ranging from ordered requests that specify the numbers of processors needed in each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…In this situation, the network performance varies greatly from communication within a parallel computer to communication between two parallel computers. Some models have been derived to evaluate the performance of so called multi site computing [24,4,9,11,13]. However in practice, such an approach has not been implemented with the possible exception of the preplanned combination of a few specific parallel computers for a specific purpose.…”
Section: Parallel Job Scheduling and The Gridmentioning
confidence: 99%
“…In this situation, the network performance varies greatly from communication within a parallel computer to communication between two parallel computers. Some models have been derived to evaluate the performance of so called multi site computing [24,4,9,11,13]. However in practice, such an approach has not been implemented with the possible exception of the preplanned combination of a few specific parallel computers for a specific purpose.…”
Section: Parallel Job Scheduling and The Gridmentioning
confidence: 99%
“…Finally, they presented results showing that the use of partitioned configuration did not necessarily imply a performance drawback [21] . Another important research about co-allocation or multisite site scheduling is presented in [22][23][24][25][26][27][28][29][30][31] . Bucur and Epema [22][23][24] assess the influence on the mean response time of the job structure and size, the sizes of the clusters in the system, the ratio of the speeds of local and wide-area communications, and of the presence of a single or of multiple queues in the system.…”
Section: Multisite Job Schedulingmentioning
confidence: 99%
“…Another important research about co-allocation or multisite site scheduling is presented in [22][23][24][25][26][27][28][29][30][31] . Bucur and Epema [22][23][24] assess the influence on the mean response time of the job structure and size, the sizes of the clusters in the system, the ratio of the speeds of local and wide-area communications, and of the presence of a single or of multiple queues in the system. Also, they evaluated different scheduling policies for co-allocation, with unordered requests, in multicluster systems with space sharing for rigid multicomponent jobs [25][26][27][28] .…”
Section: Multisite Job Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…The support of multi-site parallel execution [12,13,14,15,16] on a computational grid has been examined in previous works, concerning the execution of a job in parallel at different sites. Under the condition of a limited communication overhead, the results from our previous work [10] and from [1,3,4] all showed that multi-site parallel execution can improve the overall average response time.…”
Section: Related Workmentioning
confidence: 99%